Lyudmila Michailovna Ogorodova - Editorial Article (Бюллетень сибирской медицины)
The paper presents the creative biography of L.M. Ogorodova, clinician scientist, pediatrician, corresponding member of RAMS, professor, head of the chair of faculty pediatrics (with the course of children diseases), pro-rector on scientific research and postgraduate education of the Siberian State Medical University (Tomsk).